MANAJEMEN PENDIDIKAN AKHLAK - Sriwardona; Lutfiyani Lutfiyani; Yulda Dina Septiana; Yenni Yenni; Salman Salman; Nofrizal Nofrizal (TARBIYA ISLAMIA : Jurnal Pendidikan dan Keislaman, 2023)
Students of SMKN 1 Pasaman are multicultural because they have a variety of educational backgrounds, languages, religions, ethnicities and cultures. The diversity of students is not something that prevents the school from fostering the morals of its students. The principal of SMKN 1 Pasaman fosters the morals of multicultural students through the management of moral education. This research is interesting to study with the aim of describing the management of moral education for multicultural students that accumulates in planning, organizing, implementing, controlling, and evaluating moral education. This qualitative research uses a descriptive method with data collection techniques of observation, interviews and documentation, the data collected is analyzed and tested for validity through triangulation. The results of his research that 1) moral education is carried out through careful planning and written in the RPP, 2) it is organized that all parties have an obligation to foster the morals of multicultural students, 3) implementation of moral education for multicultural students a) carried out by the homeroom teacher directly b) moral development by the homeroom teacher with the subject teacher, c) moral development in collaboration with the homeroom teacher and the counseling teacher, d) student moral development with school leaders, e) coaching student morals with parents, 4) control and supervision are also carried out directly and indirectly, systematic 5) evaluation of moral education begins with guidance, direction, guidance, sanctions and cooperation